Kedudukan Bank Syariah dalam Penyelesaian Sengketa Melalui Arbitrase (Studi Perbandingan Indonesia dan Malaysia) - Muhammad Adil Maulana; Abdullah Kelib (Magister Kenotariatan Universitas Diponegoro, 2023)
AbstractThe development of Islamic banking into the global financial industry led to the development of Islamic banking products. It is possible there will be disputes relating to Islamic banking products. and requires a legal framework for dispute resolution truly